Access Channel Selection for WLAN using Fuzzy Expert System - Maqhat, Bakeel; Dani Baba, Mohd; Ab Rahman, Ruhani; Saif, Anwar (International Journal of Engineering and Technology, 2018)
The tremendous increase in user demands for multimedia applications with its various quality of service (QoS) requirements has become essential for the operators to accommodate the demand for real-time services in IEEE 802.11 WLAN network. Scheduling mechanism is one of the challenging issues still open for research to fully support the various QoS requirements. In this paper, scheduling scheme is proposed to manage the channel access parameter between competitive nodes. An embedded fuzzy expert system is used to dynamically allocation these parameters to the competitive stations. The simulation results show that the proposed algorithm manages to optimize the overall system utilization.Â Â